The role of DNA methylation on Octopus vulgaris development and their perspectives - Díaz-Freije, Eva; Gestal, Camino; Castellanos-Martínez, Sheila; Morán, Paloma (Frontiers in Physiology, 2014)
DNA methylation is a common regulator of gene expression and development in mammalian and other vertebrate genomes. DNA methylation has been studied so far in a few bivalve mollusk species, finding a wide spectrum of levels. We focused our study in the common octopus, Octopus vulgaris, an important organism for neuroscience, physiology and ethology research as well as for human consumption. We aim to confirm the existence of DNA methylation in O. vulgaris and ultimately, if methylation plays a role in gene regulation during octopus development. We used a genome-wide approach, methylation-sensitive amplified polymorphism (MSAP), firstly in four different tissues from the same specimens from adult benthonic individuals to test whether gene expression is regulated by methylation. Secondly, we tested the hypothesis that methylation underlies development by assessing MSAP patters from paralarvae to adult developmental stages. Our data indicate that octopus genome is widely methylated since clear differences can be observed, and the methylation pattern change with the development. The statistical analyses showed significant differences in methylation pattern between paralarvae, where higher internal cytosine methylation is observed, and the three other post-hatching stages. This suggests an important role of cytosine methylation during the first step of development, when major morphological changes take place. However, methylation seems to have little effect on gene expression during the benthonic phase, since any significant effect was revealed in the AMOVA performed. Our observations highlight the importance of epigenetic mechanism in the first developmental steps of the common octopus and open new perspectives to overcome high mortality rate during paralarvae growth. Thus, better understanding the molecular regulation patterns could lead to new approaches that increase the efficiency of husbandry of this emergent species for aquaculture.